2020
DOI: 10.1111/dth.14186
|View full text |Cite
|
Sign up to set email alerts
|

Coronavirus disease 2019 in a psoriatic patient with concomitant chronic obstructive pulmonary disease under treatment with risankizumab

Abstract: With the emergence of the coronavirus disease 2019 (COVID-19) pandemic, concern has risen among physicians if treatment with biologic agents for psoriasis may result in a more severe disease course. 1,2 To date, only a limited number of cases have been published on the outcomes of COVID-19 infection in psoriatic patients under guselkumab, ustekinumab, adalimumab and secukinumab treatment, 3-5 yet no such case was reported on patients receiving risankizumab therapy. Here, we report on a 77-year-old male patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…COVID-19 is an infectious disease mainly spread by droplets . It spreads quickly and is a severe disease that poses a great threat to people's health ( Kahn et al, 2020 ; Kim et al, 2020 ; Kiss et al, 2020 ; Lim and Claydon, 2020 ). As this is a recently discovered disease, there is no conclusion on its pathogenesis and risk factors ( Djulbegovic et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…COVID-19 is an infectious disease mainly spread by droplets . It spreads quickly and is a severe disease that poses a great threat to people's health ( Kahn et al, 2020 ; Kim et al, 2020 ; Kiss et al, 2020 ; Lim and Claydon, 2020 ). As this is a recently discovered disease, there is no conclusion on its pathogenesis and risk factors ( Djulbegovic et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Data retrieved from case-control studies, cohort studies and case reports showed full recovery form COVID-19 after synthetic and biologic DMARDs treatment interruption. Rarely these patients required hospitalization [16][17][18][19][20][21]. Favorable outcomes of COVID-19 infection in patients who continued apremilast and certain biologics, such as adalimumab, ustekinumab, ixekizumab and guselkumab, were also reported [6,[22][23][24][25][26].…”
Section: Course Of Covid-19 Infection In Psoriasis Patients Receiving...mentioning
confidence: 99%
“…The pandemic of coronavirus disease (COVID- 19), a viral pneumonia caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), has raised serious concern among dermatologists and psoriatic patients receiving systemic immunomodulating/immunosuppressive treatments [1]. Plaque psoriasis is a chronic inflammatory skin disease affecting 2-3% of the general population, and approximately one-third of patients are candidates for systemic treatments because of disease severity, extensions and/or localization in sensitive or visible areas (Figure 1) [2].…”
Section: Introductionmentioning
confidence: 99%
“…Prior reports have linked Th17 to severe immune injury in SARS-CoV-2 infection [2,3]. This data has led some authors to propose that inhibition of IL23, which is essential to Th17 phenotype, may play a protective role in the setting of SARS-CoV-2 infection by attenuating key cytokines [4][5][6].…”
mentioning
confidence: 99%